Propostas e instrumentos adotados na implantação da gestão democrática em Maceió (Alagoas 1993 1996) - Silva, João Roberto da Mota (2012)
This study presents an analysis of the process of introduction of the democratic management in the schools of the municipal system of teaching in Maceió/Alagoas and the actions that transformed the teaching in the period from 1993 to 1996. The systematization of the registers of this inquiry was organized in two chapters: the first treats Maceió public politics and democratic management and the second, the democratic management in the system of teaching of Maceió, historical, reality and results. It had as objective to investigate the school impact of the schools of the municipal system during the introduction, when it take as a reference the voice of the teachers, of the technicians and of the educators administrators what were responsible authors for realization of the process. The adopted methodology leaves from a bibliographical and documentary study, through the historical registers of the actions and of the ideas that allowed to introduce the democratic management in the education in the local authority of Maceió, confronting with official documents: Federal Constitution; National Plan of Education; Law of Guidelines and Bases; Municipal Organic Law; Status of the Theaching; Rules of Schools and School Boards and Plan of Action for the Education of Maceió. It is hoped that this study can contribute to a new reflection on the educational process in school management in order to accomplish new actions to eradicate school failure and dropout, with direct management in schools and transparency in the implementation of public money